Base editing enables duplex point mutagenesis in Clostridium autoethanogenum at the price of numerous off-target mutations - Seys, François M.; Humphreys, Christopher M.; Tomi-Andrino, Claudio; Li, Qi; Millat, Thomas; Yang, Sheng; Minton, Nigel P. (Frontiers in Bioengineering and Biotechnology, 2023)
Base editors are recent multiplex gene editing tools derived from the Cas9 nuclease of Streptomyces pyogenes. They can target and modify a single nucleotide in the genome without inducing double-strand breaks (DSB) of the DNA helix. As such, they hold great potential for the engineering of microbes that lack effective DSB repair pathways such as homologous recombination (HR) or non-homologous end-joining (NHEJ). However, few applications of base editors have been reported in prokaryotes to date, and their advantages and drawbacks have not been systematically reported. Here, we used the base editors Target-AID and Target-AID-NG to introduce nonsense mutations into four different coding sequences of the industrially relevant Gram-positive bacterium Clostridium autoethanogenum. While up to two loci could be edited simultaneously using a variety of multiplexing strategies, most colonies exhibited mixed genotypes and most available protospacers led to undesired mutations within the targeted editing window. Additionally, fifteen off-target mutations were detected by sequencing the genome of the resulting strain, among them seven single-nucleotide polymorphisms (SNP) in or near loci bearing some similarity with the targeted protospacers, one 15 nt duplication, and one 12 kb deletion which removed uracil DNA glycosylase (UDG), a key DNA repair enzyme thought to be an obstacle to base editing mutagenesis. Finally, modelling of the genomic coverage of Target-AID variants targeting different protospacer adjacent motifs (PAMs) revealed that up to 85% of C. autoethanogenum coding sequences could potentially be knocked-out with Target-AID-NG, 82% with Target-AID-iSpymac, and 92% with both base editors combined. This work illustrates the strengths and weaknesses of base editors as a new multiplex genome editing tool in Clostridium bacteria. A strategy to process prokaryotic single-guide RNA arrays by exploiting tRNA maturation mechanisms is also illustrated.